Cílios e sinalização celular na obesidade - Carmona, Bruno (2022)
Aims of the study: Determine the functional relevance of cilia in the cellular response to high glucose levels. Using retinal pigment epithelium cells: assess the impact of high glucose levels on cilia assembly and morphology; study the role of cilia in the cellular response to glucose-induced stress; understand how the cilia-associated signaling pathways can be involved.